1991
DOI: 10.4098/at.arch.91-10
|View full text |Cite
|
Sign up to set email alerts
|

Frequency distribution of conception dates in a white-tailed deer herd

Abstract: . 1991. Conception dates in a whitetailed deer herd. Acta theriol. 36: 131 -140.Conception dates of white-tailed deer, Odocoileus virginianus (Zimmermann, 1780) were estimated for the breeding periods of 1974 -76 and 1984 using fall and winter -spring fetal data. Conception dates estimated from data collected in the fall were biased. This bias resulted in an earlier mean conception date than that based on information which included data from later breeding females. Mean breeding dates differed significantly be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 21 publications
2
4
0
Order By: Relevance
“…Taking into consideration the outlying values (226-237 days) of some reported gestationals, we calculated the mean fertilization date for does to be between October 23 (SD = 14.25, n = 120) and 26 (SD = 13.41, n = 120), while for yearlings it was calculated to be between October 23 (SD = 13.72, n = 29) and 27 (SD = 12.96, n = 29). Similarly to our results, Rhodes et al (1991) also found no significant differences in fertilization times of yearlings and does in the white tailed deer species.…”
Section: Resultssupporting
confidence: 91%
“…Taking into consideration the outlying values (226-237 days) of some reported gestationals, we calculated the mean fertilization date for does to be between October 23 (SD = 14.25, n = 120) and 26 (SD = 13.41, n = 120), while for yearlings it was calculated to be between October 23 (SD = 13.72, n = 29) and 27 (SD = 12.96, n = 29). Similarly to our results, Rhodes et al (1991) also found no significant differences in fertilization times of yearlings and does in the white tailed deer species.…”
Section: Resultssupporting
confidence: 91%
“…Doe fawns commonly breed on the Savannah River Site (SRS) in South Carolina (Urbston 1967(Urbston , 1976). Several investigators have described breeding and reproductive characteristics of doe fawns at SRS (Urbston 1967, Johns et al 1977, Rhodes et al 1986, 1991, Johns 1994.…”
Section: Introductionmentioning
confidence: 99%
“…Whereas adult females breed during early November, female fawns reach breeding condition during mid-December -mid-January at SRS (Rhodes et al 1991). Our results demonstrate that spermatozoan numbers and associated reproductive characteristics of adult and yearling males (Fig.…”
Section: Discussionmentioning
confidence: 52%
“…Because successful breeding requires coincident fertile periods between sexes, temporal changes in male reproductive characteristics are most meaningful when examined in relationship to the reproductive cycle of does. In our investigation, the highest mean values for all male reproductive characteristics occurred during a period that included the majority of conception dates for adult does on SRS (mean ± SE = 13 November ± 15 days; Rhodes et al 1991). Because our study did not include the earliest part of the breeding season (ie September -mid-October), higher values for reproductive characteristics could have occurred prior to the beginning of our investigation.…”
Section: Discussionmentioning
confidence: 78%